2005
DOI: 10.1111/j.1439-0442.2005.00768.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of First Line of Defence Mechanisms in the Pathogenesis of Cellulitis in Broiler Chickens: Skin Structural, Physiological and Cellular Response Factors

Abstract: The present study examined several basic attributes of first-line defence mechanisms in the skin as potential factors that may explain the susceptibility of broiler chickens to cellulitis. The variables including structural characteristics of the skin, physicochemical properties and cellular responses to the challenge with pathogens were compared between two categories of chickens, a strain of fast-growing commercial broiler chickens (susceptible to cellulitis) and leghorn chickens (resistant to cellulitis). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 29 publications
1
5
0
3
Order By: Relevance
“…Ozone acting on exposed skin may breach the skins’ barrier function and allow bacteria to penetrate the deeper layers of skin, and/or worsening the symptoms of a pre-existing infection. Animal studies have demonstrated that ozone exposure may cause structural skin damage, which may increase the permeability of the skin to bacteria [ 27 ]. The reliability of this study is enhanced by adequate controlling for the non-linear meteorological confounders, temporal trends (long-term time effects, seasonal cycle, month-of-year impact), and the weekly cycle.…”
Section: Resultsmentioning
confidence: 99%
“…Ozone acting on exposed skin may breach the skins’ barrier function and allow bacteria to penetrate the deeper layers of skin, and/or worsening the symptoms of a pre-existing infection. Animal studies have demonstrated that ozone exposure may cause structural skin damage, which may increase the permeability of the skin to bacteria [ 27 ]. The reliability of this study is enhanced by adequate controlling for the non-linear meteorological confounders, temporal trends (long-term time effects, seasonal cycle, month-of-year impact), and the weekly cycle.…”
Section: Resultsmentioning
confidence: 99%
“…Peighambari et al (Peighambari et al, 1995) showed that E. coli isolated from cellulitis lesions were more likely to induce cellulitis lesions in experimentally infected 4-week-old birds than strains of noncellulitis origin. The development of cellulitis lesions in broilers could be due to the weakness of their innate immune response, specifically their heterophils (Olkowski et al, 2005).…”
Section: Cellulitismentioning
confidence: 99%
“…Neste estudo, verificou-se que apenas a causa de condenação por dermatose, que é registrada ao abate como qualquer alteração na pele (4) , apresentou uma distribuição sazonal, com a maior ocorrência concentrada no período de inverno, nas principais regiões produtoras. As lesões cutâneas podem ter várias origens e estão relacionados principalmente com deficiências nas condições de manejo nas granjas como alta densidade de criação, excesso de umidade na cama e elevada concentração de amônia no ambiente (21)(22)(23)(24) . Os cuidados de manejo na granja devem ser constantemente monitorados no período de inverno, frente às variações de temperatura observadas principalmente no sul e sudeste do país, para minimizar a ocorrência dos fatores que predispõem à dermatose.…”
Section: Resultsunclassified